Human Resource Management Practices And Employee Performance: A Systematic Literature Review - Melanny Methasari (CV Pena Jaya Pers, 2026)
Purpose:Human Resource Management (HRM) practices are a critical strategic mechanism for organizations seeking to enhance employee performance and sustain competitive advantage. This study aims to systematically review and synthesize the role of HRM practices in improving employee performance, while identifying key dimensions, research trends, and gaps in the human resource management literature. Design/methodology/approach: This study adopts a systematic literature review approach by analyzing peer-reviewed journal articles indexed in reputable databases, namely Scopus and SINTA. The review process follows PRISMA guidelines, with clearly defined inclusion and exclusion criteria to ensure methodological rigor, transparency, and consistency. Findings: The review indicates that HRM practices have a significant positive effect on employee performance through mechanisms such as job satisfaction, organizational commitment, motivation, and employee engagement. Training and development, recruitment and selection, performance appraisal, compensation and rewards, and career development are the most frequently examined HRM practices in prior studies. Research limitations/implications: This study is limited to selected databases and publication periods, which may restrict the generalizability of the findings. Future research is encouraged to adopt longitudinal designs, examine mediating and moderating variables, and explore diverse organizational contexts, particularly in emerging economies. Practical implications:The findings provide practical insights for managers and HR practitioners in designing effective HRM practices to improve employee performance and organizational outcomes. Originality/value: This study offers an integrative synthesis of HRM research and identifies key themes and future research directions. Paper type:Literature review